1985
DOI: 10.1103/physreva.31.2854
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of spin-exchange effects in elastic and ionizing collisions of polarized electrons with polarized hydrogen atoms

Abstract: Alguard, M. J.; Gay, Timothy J. ; Hughes, V. W.; Wainwright, P.F.; Lubell, M. S.; and Raith, W. , "Experimental study of spin-exchange effects in elastic and ionizing collisions of polarized electrons with polarized hydrogen atoms" (1985). Using crossed beams of polarized electrons and polarized hydrogen atoms we have investigated the effect of spin exchange on 90° elastic scattering from 4.4 to 30.3 eV and impact ionization from 14.1 to 197.0 eV. Our results suggest that the range of validity of various theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 151 publications
9
32
0
Order By: Relevance
“…Though previous quantal calculations [15,94] are consistent with this energy independence, their scatter or insufficient penetration into the threshold region leads to some uncertainty as to the value at threshold. We reproduce our results [39] along with experiment [97] and other calculations for A s in figure 16(b). They confirm a linear, nearly energy-independent behaviour below 0.05 au and that the spin asymmetry approaches the limiting value A s = 0.54 ± 0.01.…”
Section: Spin Asymmetrysupporting
confidence: 77%
See 1 more Smart Citation
“…Though previous quantal calculations [15,94] are consistent with this energy independence, their scatter or insufficient penetration into the threshold region leads to some uncertainty as to the value at threshold. We reproduce our results [39] along with experiment [97] and other calculations for A s in figure 16(b). They confirm a linear, nearly energy-independent behaviour below 0.05 au and that the spin asymmetry approaches the limiting value A s = 0.54 ± 0.01.…”
Section: Spin Asymmetrysupporting
confidence: 77%
“…For all the singlet calculations the PECS iterative-coupling method failed to converge and solutions were obtained using our fully-coupled method (n g = 1). However, the energy perturbation method did converge over a useful range of energies, allowing solutions to be obtained for E 0.0025 au below [94], RMPS and CCC [15] calculations and measurements of Fletcher et al [97] and Shah et al [98] are also shown. E = 0.05 au and E 0.0050 au above E = 0.05 au.…”
Section: Wannier Threshold Lawmentioning
confidence: 99%
“…All dimensions shown are in mm such a manner that the spins are adiabatically rotated [6] and maintained either parallel or antiparallel to the direction of the beam by the 100 mG longitudinal magnetic field that is present at the center of the interaction region. A circular aperture 6.0 mm in diameter and located 38 mm upstream from the center of the interaction region serves to define the dimension of the beam.…”
Section: A Overviewmentioning
confidence: 99%
“…Whether used as a probe of the weak interaction [1], as a testing ground for quantum electrodynamics [2], as a laboratory for metrology [3] and .the determination of the values of fundamental constants [4], or as a target for the study of basic atomic coIlisions [5][6][7][8], the hydrogen atom has continued to play a central role in our attempt to understand physical phenomena at their most basic level. As a consequence, much effort has been devoted to the development of atomic hydrogen beams, both ground state and excited state, both polarized and un polarized [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation